The medical revolution : how technology is changing health care - Nardo, Don, 1947- (ReferencePoint Press, 2021)
Briefly explores how technology has revolutionized and advanced medical care in the twentieth and twenty-first centuries. Includes chapters on genetic engineering, nanotechnology, and how 3D printing has helped in making prostheses.